Development of Critical Thinking-Based Basic Reading Teaching Materials: Arabic Learning Innovation in Islamic Universities - Tika Mardiyah; Meidias Abror Wicaksono; Ahmad Abdul Hadi Abdul Jawad Filefil (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
This research addresses the urgent need for innovation in teaching Arabic reading skills at Islamic higher education institutions. Previous studies on Arabic learning have largely focused on literal understanding, with limited attention to fostering students’ critical thinking skills. This study aims to develop and evaluate Arabic reading materials based on critical thinking to bridge this gap. Employing a research and development method with the ADDIE model, this study was conducted at the Arabic Education Program, UIN Sayyid Ali Rahmatullah Tulungagung. Data were collected through questionnaires, tests, validation sheets, and interviews. Analysis techniques included descriptive statistics, paired sample t-test, and N-Gain. The results showed a significant improvement in students' reading abilities: post-test scores (M = 70.00) were significantly higher than pre-test scores (M = 55.14) with a p-value of 0.000 and N-Gain of 0.37 (moderate category). The developed material integrated contextual topics, critical thinking tasks, and digital tools. It effectively promoted students’ analytical and evaluative reading skills. The study concludes that reading materials incorporating critical thinking elements are pedagogically effective and relevant to current curriculum needs. Penelitian ini membahas kebutuhan mendesak akan inovasi dalam pengajaran keterampilan membaca bahasa Arab di perguruan tinggi keislaman. Penelitian-penelitian sebelumnya tentang pembelajaran bahasa Arab sebagian besar berfokus pada pemahaman literal, dengan perhatian yang terbatas terhadap pengembangan keterampilan berpikir kritis mahasiswa. Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi bahan ajar membaca bahasa Arab berbasis berpikir kritis guna menjembatani kesenjangan tersebut. Dengan menggunakan metode penelitian dan pengembangan (R&D) melalui model ADDIE, penelitian ini dilakukan pada Program Studi Pendidikan Bahasa Arab UIN Sayyid Ali Rahmatullah Tulungagung. Data dikumpulkan melalui angket, tes, lembar validasi, dan wawancara. Teknik analisis data meliputi statistik deskriptif, uji paired sample t-test, dan N-Gain. Hasil penelitian menunjukkan peningkatan yang signifikan pada kemampuan membaca mahasiswa: skor post-test (M = 70,00) secara signifikan lebih tinggi dibandingkan skor pre-test (M = 55,14) dengan nilai p = 0,000 dan N-Gain sebesar 0,37 (kategori sedang). Bahan ajar yang dikembangkan memadukan topik kontekstual, tugas berpikir kritis, dan alat digital. Bahan ajar ini terbukti efektif dalam meningkatkan kemampuan membaca analitis dan evaluatif mahasiswa. Penelitian ini menyimpulkan bahwa bahan ajar membaca yang mengintegrasikan elemen berpikir kritis bersifat efektif secara pedagogis dan relevan dengan kebutuhan kurikulum saat ini.